1990
DOI: 10.1111/j.1365-2362.1990.tb02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritable abnormal lipoprotein metabolism in Werner's syndrome similar to familial hypercholesterolaemia

Abstract: Studies were made on the abnormality of lipoprotein metabolism and its cause in 10 patients with Werner's syndrome. Seven of the 10 patients had hypercholesterolaemia (above 250 mg dl-I). Six of the seven patients with hypercholesterolaemia had thickened Achilles' tendons (> 9 mm). A significant positive correlation (P < 0.01) was found between the serum total cholesterol levels and the thickness of Achilles' tendons in these 10 patients, suggesting that the substance precipitated in the thickened tendons is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…As to hyper‐LDL cholesterolemia, Yokote and Mori et al . reported that thickened Achilles tendon and hypercholesterolemia occurred in six out of 10 Werner syndrome patients in their facilities, 47 and five of them showed a decrease in the LDL receptor activity; 51 thus, it might be plausible that Werner syndrome itself possesses some sort of mechanism to decrease the LDL receptor activity. Given that an increased LDL cholesterol level is a disease‐specific postnatal feature in Werner syndrome, it might be possible to assume that hypercholesterolemia in Werner syndrome patients has a risk equivalent to familial hypercholesterolemia considering the notion of cumulative LDL cholesterol, which has recently been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…As to hyper‐LDL cholesterolemia, Yokote and Mori et al . reported that thickened Achilles tendon and hypercholesterolemia occurred in six out of 10 Werner syndrome patients in their facilities, 47 and five of them showed a decrease in the LDL receptor activity; 51 thus, it might be plausible that Werner syndrome itself possesses some sort of mechanism to decrease the LDL receptor activity. Given that an increased LDL cholesterol level is a disease‐specific postnatal feature in Werner syndrome, it might be possible to assume that hypercholesterolemia in Werner syndrome patients has a risk equivalent to familial hypercholesterolemia considering the notion of cumulative LDL cholesterol, which has recently been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Assay of acetylated LDL degradation Degradation and binding of 1251-labelled acetylated LDL (125I1 aLDL) or 125I-LDL were assayed as reported [15,16]. Briefly, LDL was obtained from the serum of normal volunteers, and acetylated and iodinated as reported [17,18].…”
Section: Tissue Culturementioning
confidence: 99%
“…Stimulation time (h) Figure 3 Effect of length of stimulation period with PMA on degradation of 51l-aLDL by medial SMC Medial SMC were incubated with 1 x 10-8 M PMA for the indicated periods and then after changing the medium with 10 #cg/Ml 125 I-aLDL as described in the legend of degradation activities were as follows; without PMA, 0; I x 10-1°M PMA, 2.81 +0. 16 (n = 3); 1 x 10-9 M PMA, 2.76 (n = 2); 1 x 10-1 M PMA 5.39+0.12 (n = 3); 1 x 10-7 M PMA, 0.62 + 0.28 (n = 3) ,ug/mg of cell protein (mean _ S.D.). PMA at I X 10-7 M had less effect on the degradation activity of SMC, although it caused no injury of the cells detectable by microscopy or by the Trypan Blue exclusion test.…”
mentioning
confidence: 99%
“…Overall, such mutant mice have a 10–15% decreased of their mean life span [ 17 , 18 ]. Of relevance, increased oxidative stress has been described for WS subjects in addition to abnormal metabolic phenotypes [ 19 21 ]. In addition to the metabolic abnormalities found in Wrn Δhel/Δhel mice, microscopic analysis of tissues revealed three other major changes; increased levels of visceral fat tissues, defenestration of liver sinusoidal endothelial cells (an increasingly recognized morphological change associated with normal aging [ 22 ]), liver steatosis [ 23 ], and aortic stenosis [ 24 ] followed by cardiac fibrosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%